2022
DOI: 10.7573/dic.2021-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology: how to manage atopic dermatitis in patients with skin of colour

Abstract: Atopic dermatitis (AD) is a chronic inflammatory cutaneous disease prevalent in all skin types but can differ in pathogenesis and clinical presentation. It has been documented in the literature that AD is more prevalent in Asian and Black individuals than in white individuals. Genetic variations as well as cultural and socioeconomic factors have important implications for susceptibility to AD and response to treatment in skin of colour. In this narrative review, we discuss differences in the epidemiology, path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Interestingly, some differences in the clinical manifestations of AD exist among ethnic groups, which may pose diagnostic challenges. The clinical heterogeneity of AD is oftentimes the result of differences in the distribution and pigmentation of the lesions [ 8 ]. Asian individuals typically present lesions with more defined borders, sometimes closely resembling psoriasis plaques, as well as more scaling and lichenification, in comparison to white AD patients [ 9 , 10 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Interestingly, some differences in the clinical manifestations of AD exist among ethnic groups, which may pose diagnostic challenges. The clinical heterogeneity of AD is oftentimes the result of differences in the distribution and pigmentation of the lesions [ 8 ]. Asian individuals typically present lesions with more defined borders, sometimes closely resembling psoriasis plaques, as well as more scaling and lichenification, in comparison to white AD patients [ 9 , 10 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…As a consequence, the use of standardised scoring systems that rely on skin erythema, including SCORing Atopic Dermatitis and Eczema Area and Severity Index, may result in less experienced physicians significantly underappreciating the severity of AD in darker skin [4,39.40]. Other classic findings that are more commonly reported in skin of colour include Dennie-Morgan lines, diffuse xerosis, and hyperlinearity of the palms [11,47].…”
Section: Differences In Clinical Phenotype Of Ad In Australian Skinmentioning
confidence: 99%
“…18 However, current guidelines are similar across all skin types, with regular emollients and topical steroids being the mainstay of treatment for most patients with mild to moderate disease. 19 It is important to consider that topical steroids carry a greater risk…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…of hypopigmentation in darker skin. 19 Furthermore, regarding systemic treatments for severe disease, studies have found that Black patients have a higher risk of alopecia secondary to methotrexate and a lower bioavailability of ciclosporin, thus requiring higher doses. 20,21…”
Section: Eliza Hutchison Rakeb Yoseph and Hannah Wainmanmentioning
confidence: 99%